Why livestock matter for PSTA5 goals - Karugia, Joseph T.; Chan, Derek; Bahta, Sirak; Aragie, Emerta A.; Enahoro, Dolapo; Thurlow, James; Warner, James; Maruta, Admasu Asfaw; Jean-Pierre, R.P.; Rich, K.M.; Enahoro, D.K. (International Food Policy Research Institute, 2024)
Presented at Policy Seminar in Musanze, Rwanda on December 4, 2024.